THE EVOLUTION OF CONSUMER RIGHTS IN E-COMMERCE IN BRAZIL (REMUNOM, 2025)
This article analyzes the evolution of consumer rights within the scope of Brazilian e-commerce. It starts with the 1990 Consumer Defense Code (CDC) as a fundamental legal pillar, examining how its principles apply to a digital scenario unforeseen at the time of its creation. The study traces the growth trajectory of e-commerce in Brazil, highlighting the acceleration caused by the COVID-19 pandemic as an inflection point that consolidated online consumption. Specific legislations that emerged in response to this new reality are analyzed, including Decree No. 7,962/2013 (the E-commerce Law), the Brazilian Civil Rights Framework for the Internet (Marco Civil da Internet), and the General Data Protection Law (Lei Geral de Proteção de Dados Pessoais - LGPD), which introduced a new era of governance over privacy. The analysis delves into the issue of civil liability of digital platforms, with an emphasis on the understanding of the Superior Court of Justice (STJ) regarding the role of marketplaces. Finally, the article addresses contemporary challenges, such as digital fraud, dark patterns, and the pressing need for digital education to empower consumers. The objective is to offer a critical overview of the current stage of consumer protection in the digital environment and reflect on future perspectives for guaranteeing a fairer and safer online market.